The diagnostic value of soluble urokinase plasminogen activator receptor compared with C-reactive protein and procalcitonin in children with febrile neutropenia - KOÇ, AHMET; TOKUÇ, AYŞE GÜLNUR; KEPENEKLİ KADAYİFCİ, EDA; HAKLAR, GONCAGÜL; ALTINKANAT GELMEZ, GÜLŞEN; CİNEL, İSMAİL HAKKI; ŞİRİKÇİ, ÖNDER; DEMİRCİOĞLU, SERAP (TAYLOR & FRANCIS INC, 2016)
The aim of the present study was to determine the diagnostic value of soluble urokinase plasminogen activator receptor (suPAR) in pediatric patients with febrile neutropenia. A prospective case-control study was performed. Patients included 29 children with febrile neutropenia (FN) and 27 control subjects without any infection or immunosuppressive condition. Blood samples were obtained on the day of admission and on the 4th to 7th days of the hospital stay. The median (minimum-maximum) serum levels of suPAR obtained on the first day of the admission were 2.08 (0.93-9.42) and 2.22 (1.08-5.13) ng/mL for the FN group and the control group, respectively. The median serum levels of suPAR in the FN and control groups were not significantly different (P=.053). The mean serum suPAR level was significantly higher in nonsurvivors than in survivors in the FN group (P<.05). In the FN group, the area under the receiver operating characteristics curve (AUCROC) for suPAR was 0.546, but no optimum cutoff value, sensitivity, specificity, negative predictive value (NPV), or positive predictive value (PPV) was obtained. We conclude that suPAR is not useful as a diagnostic biomarker in children with febrile neutropenia; however, persistent high serum suPAR level may predict mortality in FN in children.
Keywords: Children; febril neutropenia; soluble urokinase plasminogen activator receptor; SERUM-LEVELS; CEREBROSPINAL-FLUID; PLASMA; SUPAR; CANCER; MARKERS; MALARIA; LEVEL; UPAR